Case management in early psychosis intervention programme: Perspectives of clients and caregivers. Issue 3 (14th December 2017) - Wong, Horng Hien; Yong, Yee Huei; Shahwan, Shazana; Cetty, Laxman; Vaingankar, Janhavi; Hon, Charlene; Lee, Helen; Loh, Christopher; Abdin, Edimansyah; Subramaniam, Mythily
Abstract : Aim: This qualitative study explored the perspectives of clients and caregivers on case management provided by the Singapore Early Psychosis Intervention Programme (EPIP), with the intent to understand the salient aspects of case management from their perspective. Methods: Clients and their caregivers were recruited from the EPIP outpatient clinics. Focus group discussions (FGDs) were conducted at a community centre outside the hospital with 47 clients and 19 caregivers. Facilitators were experienced researchers who were not involved in the care of the clients and trained in qualitative research methodologies. All FGDs were audio recorded and transcribed verbatim with all participants' identifiers omitted to protect confidentiality. Qualitative data analysis was conducted using thematic analysis. Results: There were 11 themes that emerged from the FGDs: therapeutic alliance, holistic monitoring, collaborative role with other care providers, counselling and guidance, crisis management, bridging role, client‐centred care, client empowerment and strength building, psychoeducation/education on illness, support and problem solving. "Problem solving" surfaced only from the client FGDs; the remaining themes were common to both groups. Conclusions: The voices of clients and caregivers are important to EPIP case management service. This study has provided insights into their perspectives, understandings and lived experiences of case management and its impact on clients and caregivers.